Simultaneous subdural and scalp EEG correlates of frontal lobe epileptic sources. Issue 2 (13th January 2014) - Ramantani, Georgia; Dümpelmann, Matthias; Koessler, Laurent; Brandt, Armin; Cosandier‐Rimélé, Delphine; Zentner, Josef; Schulze‐Bonhage, Andreas; Maillard, Louis Georges
Summary Objective To assess the visibility and detectability in scalp electroencephalography (EEG) of cortical sources in frontal lobe epilepsy (FLE) as to their localization, and the extent and amplitude of activation. Methods We analyzed the simultaneous subdural and scalp interictal EEG recordings of 14 patients with refractory frontal lobe epilepsy (FLE) associated with focal cortical dysplasia. Subdural spike types were identified and averaged for source localization and detection of their scalp EEG correlates. Both raw and averaged scalp EEG segments were reviewed for spikes, blinded to subdural segments. We further analyzed the correlation of spike‐to‐background amplitude ratios in subdural and scalp EEG. Results We identified 36 spike types in subdural EEG, corresponding to 29 distinct sources. Four of 29 sources were visible by visual evaluation of scalp EEG and six additional sources were detectable after averaging: four in the medial frontal, two in the dorsolateral gyri, two in the depth of dorsolateral sulci, and two in the basal frontal region. Cortical sources generating scalp‐detectable spikes presented a median of 6 cm2 of activated cortical convexity surface and a subdural spike‐to‐background‐amplitude ratio >8. These sources were associated with a higher number of activated subdural grid contacts and a higher subdural spike‐to‐background amplitude ratio than sources generating non–scalp‐detectable spikes. Significance Not only dorsolateral but also basal and medial sources can be detectable in FLE. This is the first in vivo demonstration derived from simultaneous subdural and scalp EEG recordings of the complementary significance of extensive source activation and higher subdural spike‐to‐background amplitude ratio in the detection of cortical sources in FLE.